The concept of Kami on Japanese Web 2011 Corpus - Subhi Akbar; Ismatul Khasanah; Sri Endah Tabiati (Universitas Brawijaya, 2018)
The concept about Kami has been discussed for a quite long time. However, it is still very relevant to investigate since the people's intelligence, and the influence of other teaching keep evolving. Many kinds of research with various perspectives have been conducted to shed light on this matter. Nevertheless, the study of Kami from a linguistic point of view is still far from adequate. In this study, we analyzed the concept of Kami as described on Japanese Web 2011 corpus as the representation of the way the Japanese consider Kami. The findings of this study are: first, the attributes of Kami consist of two categories of collocation, adjective collocation and noun collocation — each type comprises ten most frequent words collocated with Kami. Those collocations denoted the Japanese concept of Kami are evolving and influenced by Christianity. Second, the conducts of Kami are derived from 10 verb collocations where Kami stand as the subject of the clause or sentence. From that collocation, we found that Japanese regard Kami as a superpower entity who can cause fortune and misfortune to human and whom human depends on. It is similar to the way another religious adherent regarding their own God. Third, the deeds toward Kami are obtained from 10 verb collocations where Kami play a role as the object in clause or sentence. That collocations show that Kami is regarded as essential things in life, which should be treated well and at the same time be feared of.